Revisiting the Honorable Merchant: The Reshaped Role of Trust in Open Innovation. (28th December 2015) - Abu El‐Ella, Nagwan; Bessant, John; Pinkwart, Andreas
Abstract: We examine trust mechanisms in innovation within a number of inter‐ and intraorganizational contexts and outline the challenges posed by open innovation to those mechanisms. The organizational contexts that we have chosen for examination are supply chain development, clusters, and employee involvement. We argue, through an in‐depth literature review that is supported by examples, that trust is being highly reshaped to better suit the growingly open innovation environment, which in many ways resonates with the historical concept of the honorable merchant. Our findings provide a better understanding of how trust facilitates the flow of information in open innovation and show how trust is becoming increasingly intermediated. Our systematic overview provides a rich context for further empirical research and innovation management practice. © 2015 Wiley Periodicals, Inc .